2022
DOI: 10.1002/nau.24923
|View full text |Cite
|
Sign up to set email alerts
|

Do medication prescription patterns follow guidelines in a cohort of women with interstitial cystitis/bladder pain syndrome?

Abstract: To describe prescription prevalence of oral bladder pain medications among women with interstitial cystitis/bladder pain syndrome (IC/BPS) and to compare with current treatment guidelines. Methods: We sampled female patients with an ICD-9/10 diagnosis of IC/BPS (595.1/N30.10) by querying active users of the Veterans Health Administration. Medical records were reviewed to determine whether patients met IC/BPS diagnostic criteria. A cohort of women with other pelvic pain disorders was identified. Prescription pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This analysis found that IC/BPS patients were given nonnarcotic bladder pain medication more often than those with OPPCs. Despite this fact and observing that over 77% of women with IC/BPS in the study received treatment, we found that IC/BPS patients had a significant increase in the number of medications used and required multiple prescriptions for pain, highlighting the difficulty in effectively treating IC/BPS ( 20 ). These treatment findings help support the conclusion that IC/BPS have worse urologic pain compared to OPPCs as demonstrated on the GUPI.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This analysis found that IC/BPS patients were given nonnarcotic bladder pain medication more often than those with OPPCs. Despite this fact and observing that over 77% of women with IC/BPS in the study received treatment, we found that IC/BPS patients had a significant increase in the number of medications used and required multiple prescriptions for pain, highlighting the difficulty in effectively treating IC/BPS ( 20 ). These treatment findings help support the conclusion that IC/BPS have worse urologic pain compared to OPPCs as demonstrated on the GUPI.…”
Section: Discussionmentioning
confidence: 79%
“…The improvements in GUPI components in both cohorts may in part reflect these treatments. We previously conducted a retrospective analysis of women with confirmed IC/BPS and those with OPPC using the same cohort definitions to identify prescription rates of nonnarcotic pain medications used in treating these conditions ( 20 ). This analysis found that IC/BPS patients were given nonnarcotic bladder pain medication more often than those with OPPCs.…”
Section: Discussionmentioning
confidence: 99%